Permen Seksi Ratu Ceting (Persiapan Menyusui Asi Ekslusif dengan Sayur Katuk Cegah Stunting pada Ibu Hamil) - Murti Murti; Nurul Hidayah; Elysa Marini; Lisda Handayani (Faedah : Jurnal Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
Breast milk (ASI) is milk produced by mothers and contains nutrients needed by babies for the needs and development of babies. The priority problems that can be drawn from this community service are regarding the preparation and provision of exclusive breastfeeding aimed at pregnant women and women of childbearing age. The solution offered is based on the analysis of the situation and problems that have been explained previously, the author conducted a demonstration of cooking pudding made from local ingredients from katuk vegetables called "PERMEN SEKSI RATU CETING" (Preparation of Breastfeeding with Katuk Vegetables Prevents Stunting in Pregnant Women). The implementation of this community service with a cooking demonstration is one effective way to increase mothers' knowledge about the importance of preventing stunting with exclusive breastfeeding. Implementation in Sungai Tabuk Kota Village RT 06, Sungai Tabuk District. The implementation of the program begins with the preparation of exclusive breastfeeding with the aim of preventing the possibility of stunting, through the use of local vegetables. Katuk leaf vegetables which are easy to find to help prepare breast milk and facilitate breast milk, are made and served creatively which is called katuk leaf vegetable pudding. The target of this program is pregnant women and women of childbearing age.